2017
DOI: 10.1039/c7ta02562a
|View full text |Cite
|
Sign up to set email alerts
|

Indacenodithiophene: a promising building block for high performance polymer solar cells

Abstract: This review surveys recent research advances in the area of IDT-based conjugated materials for photovoltaic applications. The factors affecting the bandgaps, molecular energy levels, film morphologies, as well as the photovoltaic performance of these materials have also been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 122 publications
2
81
0
Order By: Relevance
“…As shown in Table and described in Section 3.2, a 0.2 eV smaller HOMO‐LUMO gap is found in IDTT than in IDT, which contributes to the better adsorption properties in the IDTT. Our results are consistent with findings in the field of IDT‐based polymer solar cells …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Table and described in Section 3.2, a 0.2 eV smaller HOMO‐LUMO gap is found in IDTT than in IDT, which contributes to the better adsorption properties in the IDTT. Our results are consistent with findings in the field of IDT‐based polymer solar cells …”
Section: Resultssupporting
confidence: 92%
“…In one pentacyclic IDT moiety, five aromatic rings fused into a single unit, leading to good coplanar feature and a much extended π‐conjugated system. The IDT moiety has been widely used as a crucial fabricating component to construct narrow bandgap polymers for high‐efficiency polymer photovoltaic materials . Due to the rigid structural feature and good π‐conjugation, the IDT unit has also been considered for use in DSSC dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of EWGs at the terminal thienyl units ( Figure a) have been explored in acceptor–donor–acceptor (A–D–A) nonfullerene acceptors (NFAs) for use in organic solar cells. [ 31,32 ] Several reports have also shown that these IDT‐based NFAs display promising performance in thin‐film transistor applications. [ 33,34 ] Alternative attempts have focused upon chemically modifying the core via the introduction of strong EWGs at the 4,9‐bridging positions of the IDT backbone (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…The ladder-type five membered IDT moiety features desirable and easily tunable properties such as an extended π-conjugated system, an optimal balance of electron density and a quaternary bridging carbon atom that ensures planarity and carries different side groups for solubility and film morphology. 1,2 This coplanarity and the low energetic disorder of the electron rich fused ring aromatic structure favors π-electron delocalization and charge transport. 2,8,[13][14][15][16] The attachment of side groups ensures high solubility for processing OPV 17,18 and OFET devices 5,8 from solution.…”
Section: Introductionmentioning
confidence: 99%